 Proof

Taking in account the lemma it is enough to prove that exists

F ∈

F

such that up

F

=

T

P

A

h

up

i

S

, that is that

R

=

T

P

A

h

up

i

S

is a filter.

R

is nonempty because 1

R

. Let

A, B

R

; then

∀F ∈

S

:

A, B

up

F

,

consequently

∀F ∈

S

:

A

A

B

up

F

. Consequently

A

A

B

T

P

A

h

up

i

S

=

R

.

So

R

is a filter base. Let

X

R

and

X

Y

A

; then

∀F ∈

S

:

X

up

F

;

∀F ∈

S

:

Y

up

F

;

Y

R

. So

R

is an upper set.

Corollary 8

If

A

is a meet-semilattice with greatest element

1

then

F

is a

complete lattice.

Corollary 9

If

A

is a meet-semilattice with greatest element

1

then for any

A

,

B ∈

F

up(

A ∪

F

B

) = up

A ∩

up

B

.

Theorem 33

If

A

is a join-semilattice then

F

is a join-semilattice and for any

A

,

B ∈

F

up(

A ∪

F

B

) = up

A ∩

up

B

.

Proof

Taking in account the lemma it is enough to prove that

R

= up

A∩

up

B

is a filter.

R

is nonempty because exist

X

up

A

and

Y

up

B

and

R

X

A

Y

.

Let

A, B

R

. Then

A, B

up

A

; so exists

C

up

A

such that

C

A

C

B

. Analogously exists

D

up

B

such that

D

A

D

B

. Let

E

=

C

A

D

.

Then

E

up

A

and

E

up

B

;

E

R

and

E

A

E

B

. So

R

is a filter base.

That

R

is an upper set is obvious.

Theorem 34

If

A

is a distributive lattice then for

S

∈ P

F

\ {∅}

up

\

F

S

=

n

K

0

A

. . .

A

K

n

|

K

i

[

h

up

i

S

where

i

= 0

, . . . , n

for

n

N

o

.

Proof

Let’s denote the right part of the equality to be proven as

R

. First we

will prove that

R

is a filter.

R

is nonempty because

S

is nonempty.

Let

A, B

R

. Then

A

=

X

0

A

. . .

A

X

k

,

B

=

Y

0

A

. . .

A

Y

l

where

X

i

, Y

j

S

h

up

i

S

. So

A

A

B

=

X

0

A

. . .

A

X

k

A

Y

0

A

. . .

A

Y

l

R.

Let

R

C

A

. Consequently (distributivity used)

C

=

C

A

A

= (

C

A

X

0

)

A

. . .

A

(

C

A

X

k

)

.

X

i

up

P

for some

P

S

;

C

A

X

i

up

P

; consequently

C

up

P

;

C

R

.

We have proved that

R

is a filter base and an upper set. So

R

is a filter.

Consequently the statement of our theorem is equivalent to

T

F

S

= up

1

R

.

Let

A ∈

S

. Then up

A ∈ h

up

i

S

; up

A ⊆

S

h

up

i

S

;

R

K

0

A

. . .

A

K

n

|

K

i

up

A

where

i

= 0

, . . . , n

for

n

N

= up

A

.

27